(untitled) (Bangladesh Journal of Agricultural Research, 2016)
In vitro conservation of germplasm plays a vital role in maintenance breeding and also has many advantages over the conventional system. The experimental results for conservation of Colocasia sp. also proved this. In relation to explants and osmoticum, meristem and axillary bud could be conserved for 24 months while meristem-base died after 6 months. Mannitol as osmoticum @ 4% performed nicely to conserve Colocasia upto 24 months. Only meristem and axillary bud could be conserved for 24 months with the use of 4 % mannitol. But other level of mannitol remained culture alive for varying periods (6 to 12 months). After 24 months, the plant height was 6.5 cm for the meristem and 6.4 for axillary bud. Bangladesh J. Agril. Res. 41(1): 67-74, March 2016